A method of detecting the C4 violin mode in the energy spectra of chromatic scales - Piotr Wrzeciono (Archives of Acoustics)
This article presents a method of detecting the frequency of the C4 mode of the violin in the energy spectra of chromatic scales. The recordings from the AMATI multimedia database, which includes recorded sounds of violins taking part in the 10-th Henryk Wieniawski International Violin Making Competition in Pozna´n, are used in the study. The method is based on the search for the part of the energy spectra of recorded chromatic scales which is common for these spectra. The recordings were made in the near field, separately for each string. The analysis of the spectra was made in a 650 to 796 Hz band, with the 0.5 Hz resolution. All the instruments in the AMATI database were tuned to A4 = 443 Hz. The frequencies of the strings were as follows: the G string: 196.89 Hz, the D string: 295.34 Hz, the A string: 443 Hz, the E string: 664.5 Hz.